Структурные особенности системы уголь-метан - Алексеев, А.Д.; Шаталова, Г.Е.; Ульянова, Е.В.; Молчанов, А.Н.; Письменова, Н.Е.; Левченко, Г.Г. (Физика и техника высоких давлений, 2003)
Изучена десорбция метана из твердого углеметанового раствора методами ЯМР и рентгеноструктурного анализа. Показано, что форма его существования в структуре угольного вещества определяет степень подвижности молекул метана. Рассмотрен фазовый состав природного угля, определен вид углеводородной фазы (УВФ). Предложена модель изменения структуры угля при насыщении метаном под давлением и в процессе десорбции. Methane desorption from solid methane-coal solution has been studied by NMR and X-ray diffraction analysis methods. It is shown that the form of its existence in the structure of coal substance defines the degree of the methane molecule mobility. The phase composition of fossil coal has been examined, the composition of hydrocarbon phase has been determined. A model has been proposed to describe changes in coal structure for the case of saturation with methane under pressure and during the desorption.